Sediments and Biota of the Marine Coastal Zone of Igloolik Island, Nunavut - Dale, Janis; Leontowich, Kent (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2006)
Abstract Few studies in arctic Canada have combined research on both the physical marine environment and benthic invertebrates. This is the first detailed study of the oceanographic conditions and distribution of sediments and biota in the intertidal and subtidal zones of Igloolik Island, Nunavut. Oceanographic measurements (temperature, salinity, dissolved oxygen, turbidity), and sediment and biological sampling were undertaken over two summers (1999, 2002). Intertidal zones are underlain by bedrock with a thin veneer of gravel with a very poorly sorted fine matrix and devoid of benthic invertebrates, due to harsh environmental conditions. Ninety-six benthic invertebrates species were identified in the subtidal zone of Turton Bay, a shallow embayment of Igloolik Island that opens to the south into Hooper Inlet. Oceanographic conditions were similar throughout Turton Bay. The shallow depth of Turton Bay (<25 m) and open fetch to the south means that the bay water is well mixed throughout during the ice-free period. Variations in species, abundances and densities result from local conditions and substrate characteristics. Subtidal areas with unconsolidated substrates have abundant and diversified benthic fauna, whereas those with consolidated substrates have more limited species dominated by epifauna. The greatest abundances and densities occur at the deepest sites with the finest sediments and deposit-feeding species. The shallow subtidal zone (<5 m) is characterized by a thin sandy surface veneer overlying bedrock. It is an extension of the intertidal zone and is much affected by ice action during break-up with reduced numbers of marine fauna. High densities of opportunistic and pollution tolerant species along transects in Turton Bay are explained by the outflow and seepage from the sewage lagoon and dumpsites proximal to these transects.